(untitled) (Docentes 2.0 Journal, 2024)
In 21st-century education, new objectives have gradually been implemented, from using a second language to developing digital skills. In this sense, the essay aimed to determine the effect of implementing a gamified strategy to strengthen communicative competence in primary school students in English as a foreign language. This essay was framed using the inductive method, the humanistic paradigm, a qualitative, interpretive approach, and a narrative topic design. Based on the above, the historical and investigative background and the theoretical foundation to support the effects of gamification in strengthening communicative competence in English will be disclosed. In this way, it would seek to impact the student’s academic performance in English, the performance presented in standardized tests, and their future professional development.